Mary Poppins was right: Adding small amounts of sugar or salt reduces the bitterness of vegetables. (1st July 2018) - Bakke, Alyssa J.; Stubbs, Cody A.; McDowell, Elliott H.; Moding, Kameron J.; Johnson, Susan L.; Hayes, John E.
Abstract: Only a quarter of adults and 7% of children consume recommended amounts of vegetables each day. Often vegetables are not initially palatable due to bitterness, which may lead children and adults to refuse to taste or eat them. The objective of this research was to determine if very small amounts of sugar or salt (common household ingredients) could lead to significant reductions in bitterness intensity and increased hedonic ratings of green vegetable purees. For Experiment 1, three different green vegetable purees (broccoli, spinach, and kale) were prepared with different levels of sugar (0%, 0.6%, 1.2%, and 1.8%) or salt (0 and 0.2%). Samples were evaluated using standard descriptive analysis techniques with nine adults who completed more than 20 h of green vegetable specific training as a group. For Experiment 2, each vegetable puree was prepared with either 0% or 2% sugar, and bitterness was assessed via a forced choice task with 84 adults. For Experiment 3, each vegetable puree was prepared with 0%, 1%, or 2% sugar and rated for liking on standard 9 point hedonic scales by 99 adults. Experiments 1 and 2 showed that addition of small amounts of sugar and salt each reduced the bitterness (and increased sweetness and saltiness) from all three vegetables without altering other sensory properties (e.g. texture or aroma). Experiment 3 showed that adding sugar to vegetable purees increased hedonic ratings for adult consumers. We also found parents had mixed attitudes about the idea of adding sugar to foods intended for infants and toddlers. Further research on the effects of bitterness masking especially for specific populations (e.g., infants and young children or adults who have higher sensitivity to bitter taste) is warranted.